PELATIHAN PENULANGAN BETON PADA BANGUNAN KONSTRUKSI BETON BERTULANG DI DISTRIK MERAUKE - Budi Doloksaribu; Abner Doloksaribu; Dewi Sriastuti Nababan (Musamus University, 2019)
The construction work of buildings using reinforced concrete construction is increasingly being used today in Merauke City along with the improving economic development of the community and increasing population growth so that the construction of public facilities and residential buildings start to shift from semi-permanent to permanent construction using reinforced concrete. The development is less accompanied by the availability of human resources so that service users often bring more professional builders from outside the island. This devotion aims to provide concrete training to the people of Merauke who work as builders to improve their expertise in work carried out in accordance with the increasing market demand. The result of this devotion is that participants have better ability in their profession, more competent, and better understanding the rules of construction in reinforced concrete construction so that concrete construction works properly. Keywords: reinforced concrete, construction